Aidilfitri contribution-giving ceremony / Muhammad 'Izzuddin Zamery and Dr. Gurmeet Kaur Surindar Singh - Zamery, Muhammad 'Izzuddin; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
Dr. Aida Azlina Ali, the Deputy Dean of Student Affairs at the Faculty of Pharmacy, demonstrated her compassion and dedication by personally delivering a remarkable gesture of support to a group of pharmacy students. On April 12, 2023, at the Dean's office, Faculty of Pharmacy, UiTM Puncak Alam, Dr. Aida distributed a total of five thoughtfully assembled packages to students who were unable to return to their hometowns to celebrate Hari Raya Aidilfitri with their families. Each meticulously filled package contained a variety of essential items, including dry food, traditional festive cookies, and other much-needed provisions.